Pemberdayaan Paralegal dalam Mencegah Kekerasan terhadap Perempuan di Desa Tuwed Kecamatan Melaya Kabupaten Jembrana - Ni Kadek Candra Dewi; I Nyoman Gede Sugiartha; I Made Minggu Widyantara (Warmadewa Press, 2022)
Violence against women is very common in Indonesia, especially in the Bali area which is famous for upholding patrilineal lineages which assume that a patriarchal culture is where men are above women in terms of position. This happens due to a lack of knowledge about the law, especially for the poor and marginalized. After the birth of paralegals as an implementation of Law Number 16 of 2011 concerning Legal Aid, it is very interesting to study its relation to violence against women. Thus, the purpose of this study is to analyze paralegals in preventing cases of violence against women in Tuwed Village and discuss the effectiveness of paralegals in preventing violence against women in Tuwed Village. This research uses empirical methods with a case study approach. This research uses primary data sources, namely face-to-face interviews with informants, and secondary data sources using complementary sources of legislation in the study of literature. The researcher in collecting data uses a literature review method to collect primary data, and conducts field research (interviews and questionnaires). Paralegal arrangements in preventing violence against women have been regulated in the Legal Aid Law Number 16 of 2011 concerning Legal Aid. The results of this research indicate that the role of paralegals in preventing violence against women in Tuwed Village has not been effective, due to the lack of counseling and socialization about paralegals and violence against women to the people of Tuwed Village